Aassessing degeneration of corticospinal tracts in a tdp-43 transgenic mouse model of als/ftd: application of 3d reconstruction in cleared tissue - Müller Igaz, Lionel Ivan (2021)
The neurodegenerative diseases amyotrophic lateralsclerosis (ALS) and frontotemporal dementia (FTD) represent two ends of one spectrum disorder, termed ALS/FTD. These incurable pathologies are now classified as ?TDP-43 proteinopathies?,since mislocalization and aggregation of the nuclear protein TDP-43 arehallmark features of most cases. A main feature ofALS/FTD is degeneration of the corticospinaltract (CST), composed of axons of upper motor neurons, being the main motorpathway involved in voluntary movement. We are using a novel approach,combining a cost-effective unsectioned brain/spinal cord clearing technique,fluoroRuby staining, one-photon confocal microscopy and 3D reconstruction tostudy the morphological changes in the CST of TDP-43 transgenic (TG) mice. Wehave previously shown in mice that inducible overexpression of a cytoplasmic (ΔNLS) form of TDP-43 in forebrain neurons evokesneuropathological and behavioural changes that recapitulate several features ofTDP-43 proteinopathies. Our preliminary results showed proper and consistenttracer delivery, with similar number of labelled cortical neurons in controland TG mice. TDP-43-ΔNLS expression decreased the length of cortical apicalprocesses and the number of cervical axons. Remarkably, suppression of TG expression(displaying reversible motor phenotypes) led to an increase in cervical axonalbranching. These studies will help to elucidate the mechanisms underlying themotor phenotypes in ALS/FTD.